El Contador Profesional : ¿Un Científico Del Siglo XXI? - Pérez Clavijo, Raquel Carolina (2017)
The main objective of this job is to clarify the question about which group is more acceptable to belong accounting , as a science, as a technique, or is simply a profession as an office, for this research to be investigated between the theoretical and definitions of each item and to see as well as a brief survey of a sample of 230 accounting professionals who will be evaluated in their opinions on the definitions of accounting, science, technology and the profession, in addition all the research will lead us to The conjecture that "scientist" is a qualifier for accounting professionals based on the similarities of the theories and the opinion of the respondents.